2013
DOI: 10.1177/0218492313502028
|View full text |Cite
|
Sign up to set email alerts
|

Role of renal biomarkers as predictors of acute kidney injury in cardiac surgery

Abstract: Cardiac surgery is unique in using cardiopulmonary bypass in various clinical scenarios. Injury of vital organs is unavoidable in the perioperative period. Acute kidney injury is a consequence of the systemic inflammatory response after bypass, emboli, ischemia, and low cardiac output states, reportedly occurring in 30%-40% of open heart surgeries. Acute kidney injury is associated with increased morbidity, mortality, and cost. Many preventive measures (off-pump procedures, decreased crossclamp time, pulsatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 68 publications
0
12
0
4
Order By: Relevance
“…In patients with congestive heart failure, Damman et al recently demonstrated that KIM-1 is an outstanding predictive marker for AKI detection [100]. Also, elevation of urinary KIM-1 levels was found to be correlated with increased risk of death or hospitalization among patients with congestive heart failure, independent of estimated glomerular filtration rate (GFR) [101]. In a study of 32 urinary biomarkers of AKI after cardiac surgery, incorporation of KIM-1 with IL-18 generated an AUC of 0.92, and the combination surpassed other biomarkers [99].…”
Section: Kidney Injury Moleculementioning
confidence: 99%
“…In patients with congestive heart failure, Damman et al recently demonstrated that KIM-1 is an outstanding predictive marker for AKI detection [100]. Also, elevation of urinary KIM-1 levels was found to be correlated with increased risk of death or hospitalization among patients with congestive heart failure, independent of estimated glomerular filtration rate (GFR) [101]. In a study of 32 urinary biomarkers of AKI after cardiac surgery, incorporation of KIM-1 with IL-18 generated an AUC of 0.92, and the combination surpassed other biomarkers [99].…”
Section: Kidney Injury Moleculementioning
confidence: 99%
“…Массивная гидратация, ле-карственное увеличение канальцевой секреции, потеря массы тела -не полный перечень обстоятельств, снижа-ющих эффективность применения обычных критериев ОПП для этого контингента больных [18]. Известны данные о клинической информативности определения БМ -молекул, экспрессируемых резидентными и им-мунными клетками почек в ответ на повреждение, при различных этиопатогенетических вариантах их повреж-дения [11][12][13][14][15][16]. Вместе с тем представлены только еди-ничные публикации, касающиеся сравнительного ана-лиза роли разных БМ в развитии ОПП, в том числе при ТГСК [17,20].…”
Section: Discussionunclassified
“…Из-вестно, что резидентными и иммунными клетками почки увеличивается экспрессия ряда молекул, которые могут служить биомаркерами (БМ) ранних стадий повреждения органа, когда изменения скорости клубочковой фильтра-ции (СКФ) и PCr еще отсутствуют [10][11][12]. Высокая эф-фективность определения БМ для прогнозирования не-которых этиопатогенетических вариантов ОПП показана в ряде исследований [13][14][15][16][17], однако подобные данные для ОПП при ТГСК ограничены.…”
unclassified
“…Massive infusion therapy, drug-enhanced tubular secretion, body mass losses may contribute to low efficiency of routine AKI criteria in patients following HSCT [11]. Some existing data presume potential clinical value of molecular markers, expressed by resident renal cells and local immune cell populations in certain types of kidney damage [5,6,13,[19][20][21]. Meanwhile, only scattered publications deal with comparative analysis of different MBMs in AKI following HSCT [17].…”
Section: Clinical Articlesmentioning
confidence: 99%
“…Both resident kidney cells and local immune cells are shown to enhance expression of some molecules, which may serve as biomarkers of early organ damage with still normal glomerular filtration rate (GFR) and P Cr values [19,20,22]. The efficacy of MBMs evaluation for the prediction of some etiological AKI variants has been already demonstrated [5,6,13,21]. There are, however, only scarce data concerning AKI associated with HSCT [17].…”
Section: Introductionmentioning
confidence: 99%